Parenting Patterns and Environmental Factors for Suku Anak Dalam (SAD) Toddlers at Risk of Stunting in Muaro Jambi Regency - Yurizal, Yurizal; Najmah, Najmah; Rahmiwati, Anita (Riset Informasi Kesehatan, 2024)
Background: Health problems that often occur in SAD communities are low nutritional status and poverty problems in SAD communities. Overcoming stunting requires addressing the main direct cause, namely an inadequate household and family environment. The aim of this research is to analyze parenting patterns and environmental factors for SAD toddlers at risk of stunting in Muaro Jambi Regency. Method: This research uses qualitative methodology with an ethnographic research design. The aim is to study and collect data on environmental factors and parenting patterns based on daily cultural norms and activities adopted by the SAD community in Nyogan Village. Data collection used visual methods, in-depth interviews and FGD (focus group discussions), as well as anthropometric measurements. The informants for this research were 20 people consisting of the main informants, namely 15 mothers of toddlers and 5 key informants. Results: Inadequate maternal parenting and environmental factors are the causes of stunting in SAD toddlers. Conclusion: It is necessary to optimize the mother's caring role in the practice of providing food and hygiene and environmental sanitation to prevent the risk of stunting in toddlers with SAD.